Tinjauan Hukum Islam terkait Larangan Hubungan Intim setelah Melaksanakan Perkawinan dihadapan Jenazah - Abdul Rohman (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
The Corpse Marriage Tradition is a traditional marriage tradition in a particular society, usually this traditional marriage model is carried out before the body is buried, and the process of carrying out this marriage is carried out near the body, similar to what is done by some of the community in Larangan Hamlet, Dalgan Village, District. Panceng District. Gresik. This research uses a qualitative approach, where data is collected using observation and interview methods in accordance with planned interests. The results of this research are that a buried marriage according to the view of Islamic law is valid because the conditions for harmony are met, and the legal status of the marriage is that it is permissible to carry out the traditional marriage model of dead marriage because there is no conflict with the provisions of Islamic marriage.